Hydroalkylation catalyst, preparation method thereof and hydroalkylation reaction method of benzene series
By using acidic silicon-aluminum molecular sieve and A molecular sieve introduced by modified metals in the hydroalkylation catalyst, the problem of catalyst poisoning and inactivation caused by thiophene sulfur is solved, and an efficient and stable hydroalkylation reaction is achieved, reducing process costs.
Patent Information
- Application Number
- CN202311634637.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2025-05-30
AI Technical Summary
In the prior art, thiophene sulfur in the benzene raw material causes the hydroalkylation catalyst to be easily poisoned and inactivated, and the process cost is high.
A hydroalkylation catalyst is provided, which includes acidic silicon-aluminum molecular sieve and A molecular sieve. A molecular sieve is introduced into the A molecular sieve to maintain a good pore structure, and the typing of the molecular sieve pores is used to avoid contact between metals and sulfur-containing toxicants.
This catalyst has excellent anti-thiophene sulfur poisoning ability, high catalytic activity and good stability, avoiding pre-removal of thiophene-based compounds of hydroalkylated substrates, and reducing production costs.
Smart Images

Figure CN120054617A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and particularly relates to a hydroalkylation catalyst, a preparation method thereof, and a method for the hydroalkylation reaction of benzene series compounds. Background Art
[0002] The hydroalkylation of benzene is an important method for producing cyclohexylbenzene and its isomers, which has the characteristics of short process flow and mild process conditions. However, trace sulfur impurities contained in benzene often cause the catalyst to be poisoned and inactivated. CN102333747A discloses a preparation method of a hydroalkylation catalyst, which requires that the sulfur content in the raw materials is less than 3 ppm to prevent the catalyst from being sulfur poisoned and inactivated during use. Since the sulfur species in petroleum benzene are mainly thiophene compounds, whose molecular weight and boiling point are very close to those of benzene, it is impossible to directly remove them by conventional distillation separation, and only the method of adsorption can be used for deep desulfurization.
[0003] However, the use of adsorption for deep desulfurization leads to the addition of a desulfurization unit in the reaction process, increasing the complexity of the device. And many adsorbents for benzene refining desulfurization at home and abroad mostly use precious metals such as palladium and ruthenium as the main desulfurization components. For example, CN103480325A discloses a preparation method, product and application of a palladium adsorbent for benzene refining desulfurization, and its palladium content is 0.3-1.5 wt%. The precious metal adsorbent is not only expensive, resulting in increased costs. In addition, for raw materials with a high sulfur content, the precious metal adsorbent is very likely to penetrate and lose its desulfurization ability, causing the subsequent hydrogenation catalyst to be sulfur poisoned and inactivated.
[0004] Therefore, the development of a catalyst that can resist thiophene sulfur can not only avoid the use of precious metal adsorbents, but also prevent the risk of catalyst inactivation caused by fluctuations in sulfur impurities in the raw materials. Summary of the Invention
[0005] The purpose of the present invention is to overcome the problems in the prior art that the thiophene sulfur in the benzene series raw materials causes the hydroalkylation catalyst to be easily poisoned and inactivated, and the hydroalkylation process cost of benzene series compounds is high, and to provide a hydroalkylation catalyst, a preparation method thereof, and a method for the hydroalkylation reaction of benzene series compounds. This catalyst has excellent ability to resist thiophene sulfur poisoning, high catalytic activity and good stability.
[0006] To achieve the above purpose, in the first aspect of the present invention, a hydroalkylation catalyst is provided, and the catalyst includes an acidic silica-alumina molecular sieve, an A molecular sieve, and a binder;
[0007] Wherein, the A molecular sieve contains a modified metal, and the modified metal is a metal with a hydrogenation function;
[0008] In the XRD pattern of the catalyst, the relative crystallinity of molecular sieve A is not less than 10%.
[0009] In the second aspect of the present invention, there is provided a method for preparing the above-mentioned hydroalkylation catalyst, and the preparation method includes: shaping an acidic silica-alumina molecular sieve, molecular sieve A, and a binder.
[0010] Preferably, the preparation method of molecular sieve A includes:
[0011] (1) Heat-treating a molecular sieve A precursor;
[0012] (2) Contacting the product obtained in step (1) with a solution of a soluble compound containing a modified metal, and then performing solid-liquid separation, washing, and drying;
[0013] Wherein, the solvent in the solution of the soluble compound containing the modified metal is an alcohol compound and / or a ketone compound;
[0014] (3) Calcining and reducing the product obtained in step (2).
[0015] In the third aspect of the present invention, there is provided a method for the hydroalkylation reaction of benzene series compounds, and the method includes: contacting a benzene series compound raw material and hydrogen with a catalyst under hydroalkylation reaction conditions;
[0016] Preferably, the benzene series compound raw material further contains a thiophene compound, and based on the total weight of the benzene series compound raw material, the content of thiophene sulfur is 0.01 - 2 ppm, preferably 0.05 - 1 ppm.
[0017] The hydroalkylation catalyst provided by the present invention comprises an acidic silica-alumina molecular sieve and molecular sieve A. While introducing a modified metal into molecular sieve A, a good pore structure of molecular sieve A is maintained. By utilizing the shape selectivity of the molecular sieve pores, the contact between the metal and sulfur-containing poisons is avoided, and the ability of the catalyst to resist poisoning by thiophene compounds is improved. Therefore, it is not necessary to pre-remove thiophene compounds from the hydroalkylation substrate. Description of the Drawings
[0018] Figure 1 is the XRD pattern of the catalyst prepared in Example 1 of the present invention;
[0019] Figure 2 is the long-term operation result of the catalysts prepared in Example 1 and Comparative Example 1 of the present invention. Detailed Description of the Invention
[0020] The endpoints and any values disclosed in this text for a range are not limited to the exact range or value. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, between the endpoint values of each range and individual point values, and between individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this text.
[0021] In the first aspect of the present invention, a hydroalkylation catalyst is provided, and the catalyst comprises an acidic silica-alumina molecular sieve, an A molecular sieve, and a binder;
[0022] Wherein, the A molecular sieve contains a modified metal, and the modified metal is a metal with a hydrogenation function;
[0023] In the XRD pattern of the catalyst, the relative crystallinity of the A molecular sieve is not less than 10%.
[0024] The sulfur species in petroleum benzenes are mainly thiophene compounds, whose molecular weight and boiling point are very close to those of benzene. Therefore, they cannot be directly removed by conventional distillation separation and can only be deeply desulfurized by adsorption. However, most of the adsorbents used for benzene refining desulfurization in the prior art use precious metals such as palladium and ruthenium as the main desulfurization components, which undoubtedly increases the cost of the process. If the ability of the hydroalkylation catalyst to resist thiophene sulfur can be improved, it is expected to avoid additional raw material refining steps, thereby improving the economy of the process. Based on the above concept, the inventors of the present invention creatively proposed a hydroalkylation catalyst, which comprises an acidic silica-alumina molecular sieve and an A molecular sieve. The inventors of the present invention found that while introducing a modified metal into the A molecular sieve, maintaining a good pore structure of the A molecular sieve, and utilizing the synergistic effect of the acidic silica-alumina molecular sieve and the A molecular sieve, through the shape selectivity of the pores, the contact between the metal and sulfur-containing poisons is avoided, and the ability of the catalyst to resist poisoning by thiophene compounds can be improved, so that it is not necessary to pre-remove thiophene compounds from the hydroalkylation substrate.
[0025] According to the present invention, in the XRD pattern of the catalyst, the characteristic peaks at 2θ of 10±0.5°, 12±0.5°, 16±0.5°, 21±0.5°, 23±0.5°, 26±0.5°, 29±0.5°, and 34±0.5° belong to the A molecular sieve. In the present invention, the A molecular sieve contains a modified metal, and the modified metal is introduced into the A molecular sieve by ion exchange, and at least part of the modified metal exists in the form of a simple substance. The A molecular sieve containing the modified metal maintains a good pore structure and exhibits an appropriate relative crystallinity. The relative crystallinity of the A molecular sieve is not less than 10%, preferably 10-30%.
[0026] In the present invention, the test conditions of XRD include: using the powder X-ray diffraction (XRD) method to conduct a phase analysis on the molecular sieve sample, and calculating the relative crystallinity and the framework silica-alumina ratio. The instrument used is a Rigaku D / max-1400 type X-ray powder diffractometer made in Japan. Cu-Kα radiation (wavelength is ) is adopted, the tube current is 40 mA, and the tube voltage is 40 kV. The scanning angle range for the phase analysis is 5 - 50°.
[0027] The calculation method of the relative crystallinity includes: adding up the peak areas of the characteristic peaks at 2θ = 10 ± 0.5°, 12 ± 0.5°, 16 ± 0.5°, 21 ± 0.5°, 23 ± 0.5°, 26 ± 0.5°, 29 ± 0.5°, and 34 ± 0.5° in the XRD pattern of the catalyst, and obtaining the relative crystallinity by comparison with the 4A molecular sieve standard sample. In the present invention, the A molecular sieve standard sample is prepared according to the method provided on page 158 of "Chemistry of Molecular Sieves and Porous Materials" (Second Edition).
[0028] There is no particular limitation on the type of the A molecular sieve in the present invention, and it can be at least one of 3A, 4A, and 5A molecular sieves, preferably 4A molecular sieve. In the above preferred case, it is beneficial to maximize ion exchange, thereby improving the hydroalkylation performance of the catalyst.
[0029] The selection range of the modified metal in the present invention is relatively wide, and conventional metals with hydrogenation functions in the art can be used in the present invention. For example, it can be at least one of Group VIII and Group IB metals, preferably at least one of Ru, Pt, Ni, Co, Fe, Cu, Ag, Ir, and Pd, and more preferably at least one of Ru, Pt, Ni, and Pd. In the above preferred case, it is beneficial to further improve the hydrogenation activity of the catalyst.
[0030] Preferably, based on the total mass of the A molecular sieve, the content of the modified metal in terms of elements is 0.01 - 3 wt%, preferably 0.15 - 2 wt%.
[0031] The selection range of the acidic silica-alumina molecular sieve in the present invention is relatively wide. In a preferred case, the molar ratio of silica to alumina in the acidic silica-alumina molecular sieve is 20 - 40, and further preferably 22 - 38.
[0032] In a further preferred embodiment, the acidic silica-alumina molecular sieve is selected from at least one of Hβ, HY, and HMCM-22 molecular sieves.
[0033] Preferably, the mesoporous pore volume of the acidic silica-alumina molecular sieve is not less than 0.1 mL / g, preferably 0.2 - 0.5 mL / g; in the above preferred case, it is beneficial to the diffusion of molecules and further improves the hydroalkylation performance of the catalyst.
[0034] In the present invention, the mesoporous pore volume is measured by the nitrogen physical adsorption method.
[0035] According to some preferred embodiments of the present invention, based on the total mass of the catalyst, the content of the acidic silica-alumina molecular sieve is 40 - 80 wt%, preferably 50 - 70 wt%; the content of the A molecular sieve is 5 - 25 wt%, preferably 10 - 20 wt%; the content of the binder is 15 - 35 wt%, preferably 20 - 30 wt%.
[0036] In the present invention, the contents of the respective components are obtained by elemental analysis and XRD methods.
[0037] The present invention does not particularly limit the specific type of the binder, and inorganic oxides that can be conventionally used as binders in the art can be adopted. For example, it can be an oxide of at least one of the elements in Group IIA, Group IVB, Group IIIA, and Group IVA, preferably at least one of alumina, silica, and titania.
[0038] The second aspect of the present invention provides a method for preparing the above-mentioned hydroalkylation catalyst, and the preparation method includes: shaping the acidic silica-alumina molecular sieve, the A molecular sieve, and the binder.
[0039] The present invention has no particular requirements for the shaping method, and those skilled in the art can select according to actual needs. For example, kneading shaping, extrusion shaping, etc. can be adopted.
[0040] In the present invention, the acidic silica-alumina molecular sieve, the A molecular sieve, and the binder have the same definitions as in the first aspect and will not be elaborated here. The present invention does not particularly limit the source of the acidic silica-alumina molecular sieve, which can be commercially purchased or prepared by conventional methods in the art.
[0041] The present invention also does not particularly limit the source of the A molecular sieve. According to some preferred embodiments of the present invention, the preparation method of the A molecular sieve includes:
[0042] (1) Heat-treat the A molecular sieve precursor;
[0043] (2) Contact the product obtained in step (1) with a solution of a soluble compound containing a modified metal, and then perform solid-liquid separation, washing, and drying;
[0044] Among them, the solvent in the solution of the soluble compound containing the modified metal is an alcohol compound and / or a ketone compound;
[0045] (3) Calcining and reducing the product obtained in step (2).
[0046] According to some preferred embodiments of the present invention, the A zeolite precursor is a Na-type A zeolite, and more preferably a Na-type 4A zeolite. The A zeolite precursor can be obtained by commercial purchase or prepared by a method known in the art.
[0047] Preferably, the relative crystallinity of the A zeolite precursor is 80-100%, preferably 85-95%. The crystallinity of the A zeolite precursor is the same as the test method for the relative crystallinity described above.
[0048] In the present invention, through the heat treatment in step (1), impurities such as adsorbed water molecules in the zeolite can be removed. The present invention has no particular limitation on the conditions of the heat treatment. Preferably, in step (1), the temperature of the heat treatment is 250-350°C, and the time is 1-5 h; preferably, the temperature of the heat treatment is 280-320°C, and the time is 1-3 h.
[0049] Preferably, the heat treatment is carried out in an air or nitrogen atmosphere.
[0050] In the present invention, through the contact in step (2), the modified metal is introduced into the A zeolite by ion exchange. According to the present invention, the solvent in the solution of the soluble compound containing the modified metal is an alcohol compound and / or a ketone compound. The inventors of the present invention have found in the research that in the presence of the above specific solvent, it is beneficial to maintain the pore structure of the A zeolite, improve the relative crystallinity of the modified A zeolite, thereby facilitating the shape selectivity of the zeolite pores and improving the ability of the catalyst to resist poisoning by thiophene compounds.
[0051] According to some preferred embodiments of the present invention, the alcohol compound is selected from monohydric alcohols or dihydric alcohols having 2-4 carbon atoms, preferably at least one of ethanol, ethylene glycol, isopropanol, and n-butanol.
[0052] According to some preferred embodiments of the present invention, the ketone compound is selected from ketones having 3-5 carbon atoms, preferably at least one of acetone, butanone, and pentanone.
[0053] In the present invention, the modified metal is the same as that defined in the first aspect. The present invention does not particularly limit the specific types of the soluble compounds of the modified metal, and conventional soluble organic salts or inorganic salts in the art can be used. For example, it can be at least one of nitrates, chlorides, and acid salts of the modified metal. The soluble compounds of the modified metal may also contain crystal water, which is well known to those skilled in the art.
[0054] Preferably, the concentration of the solution containing the soluble compound of the modified metal is 0.01 - 5 wt%, preferably 0.5 - 3 wt%. The concentration of the solution containing the soluble compound of the modified metal refers to the percentage of the mass of the soluble compound of the modified metal in the total mass of the solution.
[0055] The present invention has a wide selection range for the dosage of the solution containing the soluble compound of the modified metal. As long as the solution is in sufficient contact with the product obtained in step (1) and the ion exchange amount is satisfied, those skilled in the art can select according to the actual situation. Preferably, the mass ratio of the product obtained in step (1) based on dry basis to the dosage of the solution containing the soluble compound of the modified metal is 1:(2 - 25), preferably 1:(3 - 20). Adopting the above preferred implementation mode is beneficial to improving the exchange efficiency of the metal.
[0056] According to the present invention, preferably, the temperature of the contact is 25 - 100 °C, preferably 30 - 80 °C; the time of the contact is 0.5 - 8 h, preferably 0.5 - 5 h.
[0057] Preferably, the contact is carried out under stirring conditions. The present invention does not have special requirements for the stirring rate as long as it is beneficial to the sufficient contact between the solution and the product obtained in step (1).
[0058] According to the present invention, step (2) further includes: separating the solid and liquid of the contacted product, washing, and drying. The present invention does not have special requirements for the specific methods and conditions of the solid-liquid separation as long as the excess solution is removed, and conventional methods in the art can be used, such as filtration or centrifugation, etc.
[0059] The present invention also does not have special requirements for the washing method. For example, deionized water can be used for the washing. The washing can also be optionally repeated, and those skilled in the art can select according to actual needs. Preferably, the number of washing times is 1 - 3 times.
[0060] The present invention does not particularly limit the drying conditions. Preferably, the drying temperature is 80 - 200 °C, and the drying time is 10 - 30 h.
[0061] According to the present invention, in step (3), the temperature of the calcination is 300 - 650°C, preferably 450 - 620°C; the time is 2 - 20 h, preferably 4 - 10 h.
[0062] According to the present invention, through the reduction treatment described in step (3), at least part of the modified metal in the A molecular sieve is reduced to the elemental state. The present invention has no special requirements for the conditions of the reduction treatment, as long as the above reduction process can be achieved. Preferably, the reduction treatment is carried out in the presence of a reducing gas. The conditions of the reduction treatment include: the temperature is 100 - 500°C, preferably 150 - 480°C, the time is 0.5 - 12 h, preferably 2 - 10 h, and the volume space velocity of the reducing gas is 100 - 600 h -1 , preferably 200 - 400 h -1 .
[0063] Preferably, the reducing gas is hydrogen.
[0064] On the other hand, the present invention provides a method for preparing a hydroalkylation catalyst, comprising the following steps:
[0065] (1) Heat-treat the A molecular sieve precursor;
[0066] (2) Contact the product obtained in step (1) with a solution of a soluble compound containing a modified metal, and then perform solid-liquid separation, washing and drying;
[0067] Wherein, the modified metal is a metal having a hydrogenation function; the solvent in the solution of the soluble compound containing the modified metal is an alcohol compound and / or a ketone compound;
[0068] (3) Calcinate and reduce the product obtained in step (2) to obtain a metal-modified A molecular sieve;
[0069] (4) Mould the acidic silica-alumina molecular sieve, the metal-modified A molecular sieve and the binder;
[0070] Wherein, the modified metal, the acidic silica-alumina molecular sieve, the binder, etc. have the same defined ranges as those in the foregoing text.
[0071] In the third aspect, the present invention provides a method for the hydroalkylation reaction of benzene series compounds, the method comprising: contacting a benzene series compound raw material and hydrogen with a catalyst under hydroalkylation reaction conditions;
[0072] Wherein, the catalyst is the hydroalkylation catalyst described in the first aspect.
[0073] Preferably, the hydroalkylation reaction conditions include: reaction temperature of 80-200°C, reaction pressure of 0.1-2MPa, molar ratio of hydrogen to benzene series of 0.1-20, mass space velocity of benzene series of 0.1-2h -1 Further preferably, the hydroalkylation reaction conditions include: reaction temperature of 100-200°C, reaction pressure of 0.6-2MPa, molar ratio of hydrogen to benzene series of 0.2-2, mass space velocity of benzene series of 0.2-2h -1 In the present invention, the reaction pressure is gauge pressure.
[0074] According to some preferred embodiments of the present invention, the benzene series raw material includes at least one of benzene, toluene and xylene.
[0075] In particular, the method provided by the present invention is particularly suitable for benzene series raw materials containing thiophene compounds, and the content of thiophene sulfur is 0.01-2ppm, preferably 0.05-1ppm, based on the total weight of the benzene series raw materials. The molecular weight and boiling point of thiophene compounds are very close to those of benzene, so they cannot be directly removed by conventional distillation separation. Since the hydroalkylation catalyst provided by the present invention has excellent resistance to thiophene sulfur, the reaction stability is good. The method provided by the present invention is used for the hydroalkylation of benzene series, and no additional raw material refining treatment is required, which is conducive to significantly reducing production costs and improving the economy of the reaction.
[0076] The present invention will be described in detail below through examples.
[0077] Unless otherwise specified, the raw materials used in the following examples and comparative examples are commercially available.
[0078] Example 1
[0079] (1) 50 g of 4A molecular sieve powder (average pore size 4 nm, crystallinity 99%) was calcined in air at 300° C. for 2 hours and then cooled to room temperature in a desiccator;
[0080] (2) dissolving 4 g of ruthenium trichloride in 200 g of anhydrous ethanol to obtain an ethanol solution containing Ru;
[0081] (3) The molecular sieve obtained in step (1) and the solution of step (2) were fully mixed and placed in a round-bottom flask, and heated and stirred at 60° C. for 2 hours;
[0082] (4) Filter the slurry after the reaction in (3), and wash the filter cake three times with deionized water. Then dry the filter cake at 130°C for 10 hours and calcine at 500°C for 5 hours. Place the powder in a tube furnace and introduce hydrogen at a volume space velocity of 200 h / min. -1 , and reduced at 250°C for 4 hours to obtain Ru-A molecular sieve.
[0083] The elemental analysis method determined that the content of Ru element in the Ru-A molecular sieve was 0.45 wt%.
[0084] (5) Take 60 g of Hβ (beta) molecular sieve (the molar ratio of silicon oxide to aluminum oxide is 25, and the mesopore volume is 0.25 mL / g), 20 g of aluminum oxide, and 20 g of Ru-A molecular sieve, mix and knead them to obtain catalyst S1.
[0085] The XRD spectrum of the catalyst is as follows Figure 1 As shown, the relative crystallinity of molecular sieve A is 15%.
[0086] Example 2
[0087] (1) 50 g of 4A molecular sieve powder (average pore size 4 nm, crystallinity 99%) was calcined in air at 300° C. for 2 hours and then cooled to room temperature in a desiccator;
[0088] (2) dissolving 3.2 g of chloroplatinic acid in 180 g of anhydrous ethanol to obtain an ethanol solution containing Pt;
[0089] (3) The molecular sieve obtained in step (1) and the solution of step (2) were fully mixed and placed in a round-bottom flask, and heated and stirred at 70° C. for 1.5 hours;
[0090] (4) Filter the slurry after the reaction in (3), and wash the filter cake three times with deionized water. Then dry the filter cake at 120°C for 12 hours and calcine at 550°C for 6 hours. Place the powder in a tube furnace and introduce hydrogen at a volume space velocity of 300 h / min. -1 , and reduced at 280°C for 5 hours to obtain Pt-A molecular sieve. The elemental analysis method determined that the content of Pt element in the Pt-A molecular sieve was 0.3 wt%.
[0091] (5) Take 60 g of Hβ (beta) molecular sieve (the molar ratio of silicon oxide to aluminum oxide is 25, and the mesopore volume is 0.25 mL / g), 25 g of aluminum oxide, and 15 g of Pt-A molecular sieve, mix and knead them to obtain catalyst S2.
[0092] The XRD spectrum of the catalyst is Figure 1 Similarly, the relative crystallinity of molecular sieve A was calculated to be 12%.
[0093] Example 3
[0094] (1) 50 g of 4A molecular sieve powder (average pore size 4 nm, crystallinity 99%) was calcined in air at 300° C. for 2 hours and then cooled to room temperature in a desiccator;
[0095] (2) dissolving 2.5 g of palladium nitrate in 250 g of acetone to obtain an acetone solution containing Pd;
[0096] (3) The molecular sieve obtained in step (1) and the solution of step (2) were fully mixed and placed in a round-bottom flask, and heated and stirred at 50° C. for 0.5 hour;
[0097] (4) Filter the slurry after the reaction in (3), and wash the filter cake three times with deionized water. Then dry the filter cake at 120°C for 12 hours and calcine at 600°C for 4 hours. Place the powder in a tube furnace and introduce hydrogen at a volume space velocity of 280h -1 , and reduced at 260°C for 6 hours to obtain Pd-A molecular sieve.
[0098] It was measured by elemental analysis method that the content of Pd element in the Pd-A molecular sieve was 0.18wt%.
[0099] (5) Take 60 g of Hβ (beta) molecular sieve (the molar ratio of silicon oxide to aluminum oxide is 25, and the mesopore volume is 0.25 mL / g), 30 g of aluminum oxide, and 10 g of Pd-A molecular sieve, mix and knead to obtain catalyst S3. The XRD spectrum of the catalyst is similar to Figure 1 Similarly, the relative crystallinity of A molecular sieve is 11%.
[0100] Example 4
[0101] (1) 50 g of 4A molecular sieve powder (average pore size 4 nm, crystallinity 98%) was calcined in air at 300° C. for 2 hours and then cooled to room temperature in a desiccator;
[0102] (2) dissolving 24.0 g of nickel nitrate in 800 g of anhydrous ethanol to obtain an anhydrous ethanol solution containing Ni;
[0103] (3) The molecular sieve obtained in step (1) and the solution of step (2) were fully mixed and placed in a round-bottom flask, and heated and stirred at 65° C. for 4 hours;
[0104] (4) Filter the slurry after the reaction in (3), and wash the filter cake three times with deionized water. Then dry the filter cake at 130°C for 8 hours and calcine at 500°C for 8 hours. Place the powder in a tube furnace and introduce hydrogen at a volume space velocity of 200 h -1 , and reduced at 400°C for 10 hours to obtain Ni-A molecular sieve.
[0105] The elemental analysis method determined that the content of Ni in the Ni-A molecular sieve was 1.6 wt%.
[0106] (5) Take 60 g of Hβ zeolite (molar ratio of silica to alumina is 25, mesoporous pore volume is 0.3 mL / g), 20 g of alumina, and 20 g of Ni-A zeolite, knead and form them to obtain catalyst S4. The XRD pattern of the catalyst is similar to Figure 1 , and the relative crystallinity of A zeolite is 15%.
[0107] Example 5
[0108] (1) Take 50 g of 4A zeolite powder (average pore diameter is 4 nm, crystallinity is 98%) and place it in air at 300 °C for roasting for 2 hours, and cool it to room temperature in a desiccator;
[0109] (2) Dissolve 4 g of ruthenium trichloride in 200 g of absolute ethanol to obtain an ethanol solution containing Ru;
[0110] (3) After fully mixing the zeolite obtained in step (1) with the solution in (2), place it in a round-bottom flask and heat and stir it at 60 °C for 2 hours;
[0111] (4) Filter the slurry after the reaction in (3), wash the filter cake three times with deionized water. Then dry the filter cake at 130 °C for 10 hours and roast it at 500 °C for 5 hours. Place the powder in a tubular furnace, introduce hydrogen, and the volume space velocity of hydrogen is 400 h -1 , and reduce it at 250 °C for 4 hours. Obtain Ru-A zeolite.
[0112] It is measured by elemental analysis method that the content of Ru element in Ru-A zeolite is 0.38 wt%.
[0113] (5) Take 60 g of HMCM-22 zeolite (molar ratio of silica to alumina is 23, mesoporous pore volume is 0.35 mL / g), 25 g of alumina, and 15 g of Ru-A zeolite, knead and form them to obtain catalyst S5. Conduct XRD test on catalyst S5 and calculate the relative crystallinity of A zeolite to be 12%.
[0114] Example 6
[0115] (1) Take 50 g of 4A zeolite powder (average pore diameter is 4 nm, crystallinity is 98%) and place it in air at 300 °C for roasting for 2 hours, and cool it to room temperature in a desiccator;
[0116] (2) Dissolve 4 g of ruthenium trichloride in 250 g of n-butanol to obtain an n-butanol solution containing Ru;
[0117] (3) After fully mixing the zeolite obtained in step (1) with the solution in (2), place it in a round-bottom flask and heat and stir it at 80 °C for 2 hours;
[0118] (4) Filter the slurry after the reaction in (3), and wash the filter cake three times with deionized water. Then dry the filter cake at 125°C for 12 hours and calcine at 500°C for 5 hours. Place the powder in a tube furnace and introduce hydrogen at a volume space velocity of 250 h -1 , and reduced at 230°C for 5 hours to obtain Ru-A molecular sieve.
[0119] The elemental analysis method determined that the content of Ru element in the Ru-A molecular sieve was 0.43 wt%.
[0120] (5) 60 g of HMCM-22 molecular sieve (the molar ratio of silicon oxide to aluminum oxide is 23, and the mesopore volume is 0.32 mL / g), 20 g of aluminum oxide, and 20 g of Ru-A molecular sieve were mixed and kneaded to obtain catalyst S6. Catalyst S6 was subjected to XRD test, and the relative crystallinity of the A molecular sieve was calculated to be 16%.
[0121] Example 7
[0122] (1) 50 g of 4A molecular sieve powder (average pore size 4 nm, crystallinity 98%) was calcined in air at 300° C. for 2 hours and then cooled to room temperature in a desiccator;
[0123] (2) dissolving 3.6 g of chloroplatinic acid in 300 g of acetone to obtain an acetone solution containing Pt;
[0124] (3) The molecular sieve obtained in step (1) and the solution of step (2) were fully mixed and placed in a round-bottom flask, and heated and stirred at 50° C. for 4.5 hours;
[0125] (4) Filter the slurry after the reaction in (3), and wash the filter cake three times with deionized water. Then dry the filter cake at 125°C for 6 hours and calcine at 600°C for 5 hours. Place the powder in a tube furnace and introduce hydrogen at a volume space velocity of 250 h -1 , reduced at 300°C for 4.5 hours to obtain Pt-A molecular sieve.
[0126] It was measured by elemental analysis method that the content of Pt element in Pt-A molecular sieve was 0.34wt%.
[0127] (5) 60 g of HMCM-22 molecular sieve (molar ratio of silicon oxide to aluminum oxide is 28, mesopore volume is 0.400 mL / g), 20 g of aluminum oxide, and 20 g of Pt-A molecular sieve were mixed and kneaded to obtain catalyst S7. Catalyst S7 was subjected to XRD test, and the relative crystallinity of A molecular sieve was calculated to be 14%.
[0128] Example 8
[0129] (1) 50 g of 4A molecular sieve powder (average pore size 4 nm, crystallinity 98%) was calcined in air at 300° C. for 2 hours and then cooled to room temperature in a desiccator;
[0130] (2) dissolving 2.5 g of chloroplatinic acid in 300 g of anhydrous ethanol to obtain an anhydrous ethanol solution containing Pt;
[0131] (3) The molecular sieve obtained in step (1) and the solution of step (2) were fully mixed and placed in a round-bottom flask, and heated and stirred at 70° C. for 1.5 hours;
[0132] (4) Filter the slurry after the reaction in (3), and wash the filter cake three times with deionized water. Then dry the filter cake at 135°C for 8 hours and calcine at 620°C for 4.5 hours. Place the powder in a tube furnace and introduce hydrogen at a volume space velocity of 300 h / min. -1 , and reduced at 280°C for 4 hours to obtain Pt-A molecular sieve.
[0133] It was measured by elemental analysis method that the content of Pt element in the Pd-A molecular sieve was 0.26wt%.
[0134] (5) 60 g of HMCM-22 molecular sieve (the molar ratio of silicon oxide to aluminum oxide is 32, and the mesopore volume is 0.28 mL / g), 28 g of aluminum oxide, and 12 g of Pd-A molecular sieve were mixed and kneaded to obtain catalyst S8. Catalyst S8 was subjected to XRD test, and the relative crystallinity of the A molecular sieve was calculated to be 10%.
[0135] Example 9
[0136] The method of Example 1 is followed, except that 20 grams of Hβ (beta) molecular sieve (the molar ratio of silicon oxide to aluminum oxide is 35, and the mesopore volume is 0.25 mL / g), 60 grams of aluminum oxide, and 20 grams of Ru-A molecular sieve are mixed and kneaded to obtain catalyst S9.
[0137] Catalyst S9 was subjected to XRD test, and the relative crystallinity of the A molecular sieve was calculated to be 14%.
[0138] Example 10
[0139] The method of Example 1 is different in that step (3) includes: mixing the molecular sieve obtained in step (1) with the solution of step (2) at 25° C. for 10 minutes, and then performing step (4) to obtain a Ru-A molecular sieve. The Ru content in the Ru-A molecular sieve is 0.1 wt % as measured by elemental analysis.
[0140] The obtained catalyst is recorded as S10. Catalyst S10 is subjected to XRD test, and the relative crystallinity of the A molecular sieve is calculated to be 15%.
[0141] Example 11
[0142] According to the method of Example 1, the difference is that an equal mass of HZSM-5 molecular sieve (molar ratio of silicon oxide to aluminum oxide is 25, and mesoporous pore volume is 0.098 mL / g) is used to replace the Hβ (beta) molecular sieve. The obtained catalyst is denoted as S11.
[0143] The catalyst S9 was subjected to XRD testing, and the relative crystallinity of A molecular sieve was calculated to be 18%.
[0144] Comparative Example 1
[0145] According to the method of Example 1, the difference is that in step (1), an equal mass of alumina is used to replace the 4A molecular sieve powder, and then it is contacted with the ethanol solution containing Ru in the same method to obtain Ru-alumina.
[0146] Take 60 grams of Hβ (beta) molecular sieve (molar ratio of silicon oxide to aluminum oxide is 25, and mesoporous pore volume is 0.25 mL / g), 20 grams of alumina, and 20 grams of Ru-alumina, knead and mold them to obtain the catalyst DS1.
[0147] Comparative Example 2
[0148] According to the method of Example 2, the difference is that in step (1), an equal mass of alumina is used to replace the 4A molecular sieve powder, and then it is contacted with the ethanol solution containing Pt in the same method to obtain Pt-alumina.
[0149] Take 60 grams of Hβ (beta) molecular sieve (molar ratio of silicon oxide to aluminum oxide is 25, and mesoporous pore volume is 0.25 mL / g), 25 grams of alumina, and 15 grams of Pt-alumina, knead and mold them to obtain the catalyst DS2.
[0150] Comparative Example 3
[0151] According to the method of Example 3, the difference is that in step (1), an equal mass of alumina is used to replace the 4A molecular sieve powder, and then it is contacted with the acetone solution containing Pd in the same method to obtain Pd-alumina.
[0152] Take 60 grams of Hβ (beta) molecular sieve (molar ratio of silicon oxide to aluminum oxide is 25, and mesoporous pore volume is 0.25 mL / g), 30 grams of alumina, and 10 grams of Pd-alumina, knead and mold them to obtain the catalyst DS3.
[0153] Comparative Example 4
[0154] According to the method of Example 4, the difference is that in step (1), an equal mass of alumina is used to replace the 4A molecular sieve powder, and then it is contacted with anhydrous ethanol containing Ni in the same method to obtain Ni-alumina.
[0155] Take 60 g of Hβ (beta) molecular sieve (molar ratio of silica to alumina is 25, mesoporous pore volume is 0.3 mL / g), 20 g of alumina, and 20 g of Ni-alumina, knead and form them to obtain catalyst DS4.
[0156] Comparative Example 5
[0157] According to the method of Example 8, the difference is that in step (1), an equal mass of alumina is used to replace the 4A molecular sieve powder, and then it is contacted with anhydrous ethanol containing Pt in the same method to obtain Pt-alumina.
[0158] Take 60 g of HMCM-22 molecular sieve (molar ratio of silica to alumina is 32, mesoporous pore volume is 0.28 mL / g), 28 g of alumina, and 12 g of Pt-alumina, knead and form them to obtain catalyst DS5.
[0159] Comparative Example 6
[0160] According to the method of Example 1, the difference is that in step (2), 4 g of ruthenium trichloride is dissolved in 200 g of water to obtain an aqueous solution containing Ru, and then steps (3) and (4) are carried out. In the obtained Ru-A molecular sieve, the content of Ru element is 0.3 wt%.
[0161] The obtained catalyst is denoted as DS6. The catalyst DS6 is subjected to XRD test, and the relative crystallinity of A molecular sieve is calculated to be 8%.
[0162] Comparative Example 7
[0163] According to the method of Example 1, the difference is that an equal mass of HZSM-5 molecular sieve (molar ratio of silica to alumina is 25) is used to replace the 4A molecular sieve powder.
[0164] The obtained catalyst is DS7.
[0165] Test Example
[0166] The catalysts prepared by the above examples and comparative examples are used for the evaluation of the hydroalkylation reaction of benzene.
[0167] The benzene raw material used contains 1 ppm of thiophene. The mass space velocity of benzene is 1 h -1 , the molar ratio of hydrogen to benzene is 2, the reaction temperature is 150 °C, and the reaction pressure is 0.1 MPa. The results of the reaction for 100 hours are shown in Table 1, and the long-term test results of the catalysts prepared in Example 1 and Comparative Example 1 are shown in Figure 2, where cyclohexane is the hydrogenation product and cyclohexylbenzene is the hydroalkylation product.
[0168] Among them, benzene conversion rate (%) = (mass fraction of benzene in raw material - mass fraction of benzene in product) / mass fraction of benzene in raw material × 100%;
[0169] Cyclohexane yield (%) = mass fraction of cyclohexane in product × (mass fraction of benzene in raw material - mass fraction of benzene in product) × 100%;
[0170] Cyclohexylbenzene yield (%) = mass fraction of cyclohexylbenzene in product × (mass fraction of benzene in raw material - mass fraction of benzene in product) × 100%.
[0171] Table 1
[0172]
[0173]
[0174] It can be seen from Table 1 that the hydroalkylation catalyst provided by the present invention has high yields of cyclohexane and cyclohexylbenzene after continuous reaction for 100 h. Combining with Figure 2 the long-term operation result diagrams of the catalysts in Example 1 and Comparative Example 1 of the present invention, it can be known that during the long-term operation process, the catalyst of the present invention can maintain high activity without decline, while the benzene conversion rate in Comparative Example 1 is low and the decline rate is faster with the running time. The above results show that the hydroalkylation catalyst provided by the present invention is little affected by the poison sulfur and has strong ability to resist thiophene sulfur.
[0175] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, including any other suitable combination of each technical feature. These simple modifications and combinations should also be regarded as the content disclosed by the present invention and fall within the protection scope of the present invention.
Claims
1. A hydroalkylation catalyst, characterized in that, the catalyst comprises an acidic silica-alumina molecular sieve, A molecular sieve and a binder; wherein, the A molecular sieve contains a modified metal, and the modified metal is a metal with hydrogenation function; in the XRD pattern of the catalyst, the relative crystallinity of the A molecular sieve is not less than 10%.
2. The catalyst according to claim 1, wherein, in the XRD pattern of the catalyst, the relative crystallinity of the A molecular sieve is 10-30%.
3. The catalyst according to claim 1, wherein, the A molecular sieve is 4A molecular sieve; preferably, the modified metal is selected from at least one of Ru, Pt, Ni and Pd; preferably, based on the total mass of the A molecular sieve, the content of the modified metal in terms of element is 0.01-3 wt%, preferably 0.15-2 wt%.
4. The catalyst according to any one of claims 1-3, wherein, the molar ratio of silica to alumina in the acidic silica-alumina molecular sieve is 20-40; preferably, the mesoporous pore volume of the acidic silica-alumina molecular sieve is not less than 0.1 mL / g, preferably 0.2-0.5 mL / g; preferably, the acidic silica-alumina molecular sieve is selected from at least one of Hβ, HY and HMCM-22 molecular sieves.
5. The catalyst according to any one of claims 1-4, wherein, based on the total mass of the catalyst, the content of the acidic silica-alumina molecular sieve is 40-80 wt%, preferably 50-70 wt%; the content of the A molecular sieve is 5-25 wt%, preferably 10-20 wt%; the content of the binder is 15-35 wt%, preferably 20-30 wt%; preferably, the binder is an oxide of at least one of Group IIA elements, Group IVB elements, Group IIIA elements and Group IVA elements; preferably at least one of alumina, silica and titanium oxide.
6. The preparation method of the hydroalkylation catalyst according to any one of claims 1-5, the preparation method comprises: shaping the acidic silica-alumina molecular sieve, A molecular sieve and the binder.
7. The preparation method according to claim 6, wherein, the preparation method of the A molecular sieve comprises: (1) Heat-treating the A molecular sieve precursor; (2) Contacting the product obtained in step (1) with a solution of a soluble compound containing a modified metal, and then performing solid-liquid separation, washing and drying; wherein, the solvent in the solution of the soluble compound containing a modified metal is an alcohol compound and / or a ketone compound; (3) Calcining and reducing the product obtained in step (2).
8. The preparation method according to claim 7, wherein, the A molecular sieve precursor is a Na-type A molecular sieve, further preferably a Na-type 4A molecular sieve; preferably, the relative crystallinity of the A molecular sieve precursor is 80-100%; preferably, in step (1), the temperature of the heat treatment is 250-350 °C and the time is 1-5 h; preferably, the heat treatment is carried out in an air or nitrogen atmosphere.
9. The preparation method according to claim 8, wherein, the alcohol compound is selected from monohydric alcohols or dihydric alcohols having 2 to 4 carbon atoms, preferably at least one of ethanol, ethylene glycol, isopropanol and n-butanol; preferably, the ketone compound is selected from ketones having 3 to 5 carbon atoms, preferably at least one of acetone, butanone and pentanone; preferably, the concentration of the solution of the soluble compound containing the modified metal is 0.01-5 wt%; preferably, the mass ratio of the product obtained in the step (1) based on dry basis to the amount of the solution of the soluble compound containing the modified metal is 1:(2-25), preferably 1:(3-20); preferably, the temperature of the contact is 25-100 °C, preferably 30-80 °C; the contact time is 0.5-8 h, preferably 0.5-5 h.
10. The preparation method according to claim 8 or 9, wherein, the calcination temperature is 300-650 °C and the time is 2-20 h; Preferably, the reduction treatment is carried out in the presence of a reducing gas, and the conditions of the reduction treatment include: the temperature is 100-500 °C, the time is 0.5-12 h, and the volumetric space velocity of the reducing gas is 100-600 h -1 .
11. A method for the hydroalkylation reaction of benzene series compounds, characterized in that, the method comprises: under hydroalkylation reaction conditions, bringing a benzene series compound raw material and hydrogen into contact with a catalyst; wherein, the catalyst is the hydroalkylation catalyst according to any one of claims 1-5; Preferably, the hydroalkylation reaction conditions include: a reaction temperature of 80 - 200 °C, a reaction pressure of 0.1 - 2 MPa, a molar ratio of hydrogen to benzene series compounds of 0.1 - 20, and a mass space velocity of benzene series compounds of 0.1 - 2 h -1 .
12. The method according to claim 11, wherein, the benzene series compound raw material includes at least one of benzene, toluene, xylene and ethylbenzene; preferably, the benzene series compound raw material further contains thiophene compounds, and based on the total weight of the benzene series compound raw material, the content of thiophene sulfur is 0.01-2 ppm, preferably 0.05-1 ppm.
Citation Information
Patent Citations
Process for producing cyclohexylbenzene
CN102333747A
Preparation method of benzene refined desulfurized palladium adsorbent as well as product and application thereof
CN103480325A